Prophetic Nomadism: An Art School Sustainability‐Oriented Educational Aim?. (October 2016) - Gunn, Vicky
Abstract: This discursive article proposes that the learning and teaching regimes provided within art school are uniquely placed within higher education to foster nomads. It suggests, however, that nomadism is not enough. Rather it emphasises that to reconcile art and design education with sustainability, such nomadism needs both to be prophetic and collaboratively based. Prophetic nomads are defined here as mobile, social influencers able to change perspectives through calling forward uncomfortable awakenings. They achieve this by creatively reframing what is at stake if we continue to act and be as we are. The presentation will explore the similarities between key concepts in the literacy of sustainability and the elements of prophetic nomadism. It will challenge us to reconsider these in the light of their potential generation through three ingredients of learning within art and design: reason, aesthetics and making. It will finish by declaring that as educators we should have the courage to more formally craft our pedagogies to call forth (evoke) and push‐out (provoke) sustainability‐oriented creativity through these domains.